ANDROID-BASED FOR FIQH SCIENCE LEARNING - Zakaria, Nizar (Letters in Information Technology Education (LITE), 2018)
With development of internet technology, mobile-learning models began to be developed. M-learning is a conventional form of learning as outlined in digital format through internet technology. This system can be used in distance learning or conventional learning. Therefore developing this model does not merely present subject matter to the internet but needs to be considered logically and holds the principles of learning. Likewise, the development design that is simple, personal, and fast, and the element of entertainment will make students feel convenience studying in front of the internet as if they were learning in class.